African yam bean: morphology, clonal propogation and nitrogen fixation - Oagile, Otsoseng (2005)
Morphological and growth observations made on landraces of African yam bean (AYB) used in this study confirm that this species is the most morphologically variable in the genus (Potter, 1992). Morphological characters such as seed colour, stem colour, internode length, leaf size and number of leaves per plant were found to vary between landraces. Growth and development was controlled by both genotype and environment. Flowering was observed only when plants were grown at 25°C, rather than at 30°C, with a 12 h photoperiod. Tuber formation occurred only in AYBS and not in other landraces. Growth rates differed between landraces and between environments with plants grown in the soil displaying faster growth than those grown in pots. The response to the environment (pot and soil experiment) differed between landraces, i.e. AYB1 performed better than AYB2 in the pot experiment, whereas it was surpassed by AYB2 in the soil experiment.